2021
DOI: 10.1097/mao.0000000000003349
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Prescribing Patterns After Skull Base Surgery for Vestibular Schwannoma

Abstract: Objective: Excessive opioid prescription is a source of prescription diversion and could contribute to chronic opioid abuse. This study describes the opioid prescribing patterns and risk factors for additional opioid prescription after surgical resection of vestibular schwannoma (VS). Study Design: Retrospective chart review. Setting: Single tertiary referral center. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
0
1
Order By: Relevance
“…Previous studies have demonstrated an association between lower opioid prescriptions and advanced age (32), which is perhaps related to a perceived increased risk of falls and overdose in the setting of polypharmacy in the elderly population (33,34). Although Ren et al (35) identified an association between higher BMI and the need for additional opioid prescriptions, the current study found no differences in opioid prescriptions between BMI groups. Although African American race has been associated with lower opioid prescriptions but higher rates of opioid refill requests (36,37), the current study found no association.…”
Section: Discussioncontrasting
confidence: 92%
“…Previous studies have demonstrated an association between lower opioid prescriptions and advanced age (32), which is perhaps related to a perceived increased risk of falls and overdose in the setting of polypharmacy in the elderly population (33,34). Although Ren et al (35) identified an association between higher BMI and the need for additional opioid prescriptions, the current study found no differences in opioid prescriptions between BMI groups. Although African American race has been associated with lower opioid prescriptions but higher rates of opioid refill requests (36,37), the current study found no association.…”
Section: Discussioncontrasting
confidence: 92%